Rendemen dan Komposisi Kimia Biji Sorgum yang disosoh dengan Alat Sosoh Batu Gurinda - S. Iskandar; D. Zainuddin; I.P. Kompiang (Buletin Ilmu Makanan Ternak, 1991)
Nutritive value of sorghum grain can be improved by separating the pericarp (bran) from its endotherm (polished grain) with grindstone polisher. Laboratory scale grindstone polisher,